"Cut‐and‐Paste" Manufacture of Multiparametric Epidermal Sensor Systems. (23rd September 2015) - Yang, Shixuan; Chen, Ying‐Chen; Nicolini, Luke; Pasupathy, Praveenkumar; Sacks, Jacob; Su, Becky; Yang, Russell; Sanchez, Daniel; Chang, Yao‐Feng; Wang, Pulin; Schnyer, David; Neikirk, Dean; et al.
Abstract : Multifunctional epidermal sensor systems (ESS) are manufactured with a highly cost and time effective, benchtop, and large‐area "cut‐and‐paste" method. The ESS made out of thin and stretchable metal and conductive polymer ribbons can be noninvasively laminated onto the skin surface to sense electrophysiological signals, skin temperature, skin hydration, and respiratory rate.